Troublesome convergences - Schiffauer, Werner (2007)
Abstract: Post-9/11 developments in the UK and Germany contrast. On the one hand, in the UK, as a consequence of the 'War on Terror', a group which had been promised participation in a multicultural society has been increasingly stigmatized and branded with 'otherness'. On the other hand, in Germany, groups that had previously been 'outside' as 'foreigners' are being selectively accepted into German society, but the groups which are excluded from this process (and even more branded with 'otherness') are notably the Muslims. These different trajectories led to different reactions: embitterment, disappointment and anger in the UK, and cynicism and resignation in Germany. An overall convergence of policies toward Islam is observable not only in Germany and the UK but throughout Europe. It seems to be more related to the construction of a collective European identity than to Islam itself